Pemanfaatan Lagu One Call Away untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris pada Siswa MTs Terpadu Berkah Palangka Raya - Maulidina Tri Amanda; Hesty Widiastuty; Misda Amallia Tuah Aji (Jurnal Kabar Masyarakat, 2024)
This study aims to enhance students' English vocabulary mastery through the use of the song One Call Away as a learning medium. The results indicate that this method effectively increases students' vocabulary, with test scores improving by an average of 25 points. Additionally, students displayed high enthusiasm and active engagement during learning sessions, making the learning process more interactive and enjoyable. The use of the song proved helpful for students in memorizing new vocabulary more easily in relevant contexts.